2013
DOI: 10.4028/www.scientific.net/amr.798-799.1033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfur Dioxide Treatment on Storage Quality and SO<sub>2 </sub>Residue of Victoria Grape<sub> </sub>

Abstract: Taking Victoria Grape as material, studied on the effect of 1000, 500 and 100 μL/L SO2 fumigation treatments on postharvest quality and SO2 residue of fruit stored under 0 °C. The results indicated that after 60 days of storage, all treatment could decrease the decay rate, inhibited the decrease of soluble solids content. The 500 μL/L SO2 fumigation treatment showed an ability to inhibit increasing of MDA content and PPO activity. The SO2 residue in grape pulp treated by 500 μL/L and 100 μL/L of SO2 were 8.31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
3
0
2
Order By: Relevance
“…1, Table 1) indicated that SO 2 treatment maintained the postharvest quality of ‘Thompson Seedless’ grapes during storage. Similar results have been reported in other studies in which SO 2 prevents degradation of TSS and reduction in weight loss and firmness 27,28 . A previous study indicated that SO 2 causes a large‐scale transcriptional response in postharvest grape berries, and the kinds and numbers of transcriptional changes were significantly higher than those induced by salicylic acid and methyl jasmonate 16 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…1, Table 1) indicated that SO 2 treatment maintained the postharvest quality of ‘Thompson Seedless’ grapes during storage. Similar results have been reported in other studies in which SO 2 prevents degradation of TSS and reduction in weight loss and firmness 27,28 . A previous study indicated that SO 2 causes a large‐scale transcriptional response in postharvest grape berries, and the kinds and numbers of transcriptional changes were significantly higher than those induced by salicylic acid and methyl jasmonate 16 .…”
Section: Discussionsupporting
confidence: 89%
“…Similar results have been reported in other studies in which SO 2 prevents degradation of TSS and reduction in weight loss and firmness. 27,28 A previous study indicated that SO 2 causes a large-scale transcriptional response in postharvest grape berries, and the kinds and numbers of transcriptional changes were significantly higher than those induced by salicylic acid and methyl jasmonate. 16 Moreover, some microRNAs were shown to be differentially expressed in response to SO 2 fumigation in 'Muscat Hamburg' grape.…”
Section: Discussionmentioning
confidence: 98%
“…Bunda depolama sıcaklığının düşük olması ve SO 2 uygulamasının solunumu azaltıcı etkisi önemlidir (Wills et al, 1998;Thompson et al, 2002;Karaçalı, 2012). Lu et al (2013) Victoria üzümünde 1000, 500 ve 100 μL/L SO 2 fümigasyonu ile 0°C sıcaklıkta 60 günlük depolama süresince suda çözünebilir kuru madde miktarındaki azalmanın engellendiğini bildirmiştir.…”
Section: Kalite Parametreleriunclassified
“…Mustonen (1992), 10 haftalık depolama sonrası hem Botrytis cinerea inoküle edilmiş hem de inoküle olmayan Calmeria üzüm çeşidinde çift salınımlı özelliğine sahip SO 2 petlerinin kullanıldığı üzümlerin sağlam ve pazarlanabilir durumda olduğunu bildirmiştir. Victoria üzümünde 1000, 500 ve 100 μL/L SO 2 fümigasyonu ile 0°C sıcaklıkta 60 günlük depolama sonrası çürüklük gelişiminin sınırlandırıldığı saptanmıştır (Lu et al, 2013). Çürüklük etmeni olarak ana etmenin Botrytis cinerea fungusu olduğu, bunun yanında az miktarda Alternaria alternata, Aspergillus spp., Penicillium spp.…”
Section: çüRüklük Gelişimiunclassified